2011
DOI: 10.1016/j.biomaterials.2011.08.073
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel design for cartilage tissue engineering: A case study with hyaluronic acid

Abstract: Hyaline cartilage serves as a low-friction and wear-resistant articulating surface in load-bearing, diarthrodial joints. Unfortunately, as the avascular, alymphatic nature of cartilage significantly impedes the body’s natural ability to regenerate, damage resulting from trauma and osteoarthritis necessitates repair attempts. Current clinical methods are generally limited in their ability to regenerate functional cartilage, and so research in recent years has focused on tissue engineering solutions in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
350
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(351 citation statements)
references
References 116 publications
1
350
0
Order By: Relevance
“…While chitosan appeared to best support the chondrogenic phenotype of MSCs in vivo, with retention of the sGAG matrix again perhaps occurring through the polycation-polyanion mechanism described above, a sufficiently stable chondrogenic phenotype was not achieved as evident by a reduction in collagen type II and an increase in collagen types I and X production and matrix calcification. A previous study comparing the capacity of various hydrogels to support stable chondrogenesis of adipose derived stem cells in vivo reported suppression of calcification by Matrigel [26]. However, when the source of stem cells was changed from adipose tissue to bone marrow, as used in this study, Matrigel calcification was also reported.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…While chitosan appeared to best support the chondrogenic phenotype of MSCs in vivo, with retention of the sGAG matrix again perhaps occurring through the polycation-polyanion mechanism described above, a sufficiently stable chondrogenic phenotype was not achieved as evident by a reduction in collagen type II and an increase in collagen types I and X production and matrix calcification. A previous study comparing the capacity of various hydrogels to support stable chondrogenesis of adipose derived stem cells in vivo reported suppression of calcification by Matrigel [26]. However, when the source of stem cells was changed from adipose tissue to bone marrow, as used in this study, Matrigel calcification was also reported.…”
Section: Discussionmentioning
confidence: 61%
“…They can be derived from natural materials which are either components of, or have macro-molecular properties similar to, native extra-cellular matrix [17], and a number of naturally derived hydrogels have been shown to support chondrogenesis of MSCs in vitro [18][19][20][21][22]. Previous studies have compared the chondrogenic capabilities of MSC-seeded hydrogels in vitro [23][24][25][26], and also the potential of chondrogenically primed MSC-seeded hydrogels to maintain a stable chondrogenic phenotype in vivo [27][28][29]. However, little is known about the capacity of different MSCseeded hydrogels to support the development of either phenotypically stable cartilage or endochondral bone in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Still chondrogenesis took place in alginate/HA, indicated by comparable levels of Col2 and ACAN gene expression after 28 d of culture in chondrogenic medium for all four hydrogels. Since positive findings were reported for the use of HA both clinically and in laboratory settings (Grigolo et al, 2001;Kavalkovich et al, 2002;Facchini et al, 2006;Liao et al, 2007;Rampichova et al, 2010;Kim et al, 2011;Erickson et al, 2012), we still believe that HA can be beneficial for cartilage tissue engineering purposes, albeit not in the current combination of high molecular weight HA with alginate. Therefore, besides alginate and fibrin, HA-pNIPAM was used to prepare hBMSC-hydrogel constructs in the osteochondral biopsy model.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, we confirmed the delivery of biologically active GFs from our scaffolds, and that the released GFs are sufficient by themselves to drive hMSC cultures towards the formation of cartilage-type tissue. While several works have shown that the combination of 3D cultures with controlled delivery of GFs is a potential strategy to induce cartilage regeneration [40], this study is one of the first testing cartilage formation driven only by the two GFs released from the scaffold. We believe that the sustained delivery of the GFs from the scaffold could result in a transport advantage over media supplementation already under in vitro culture conditions: once the extracellular matrix starts to form, it could prevent the transport of the GFs to the cells in the inner regions of the scaffold.…”
Section: Chondrogenic Differentiation In Scaffolds Delivering Tgf-β3 mentioning
confidence: 99%